Analysis of Social Sensitivity Through A'Maudu's Local Culture at SDN No. 101 Pattallassang Presidential Instruction, Pattallassang District, Takalar Regency - Suharni Herman; Abdul Azis Muslimin; Idawati I (Universitas Pendidikan Indonesia (UPI), 2023)
This thesis discusses the analysis of social sensitivity through a'maudu local culture a'maudu at SDN No. 101 Pattallassang Presidential Instruction, Pattallassang District, Takalar Regency. The formulation of the problem in this thesis are: 1) How is the social sensitivity formed in the implementation of local a'maudu culture at SDN No. 101 Pattallassang Presidential Instruction, Pattallassang District, Takalar Regency. 2) How are supporting faculties and inhibitors of the formation of social sensitivity in the implementation of local culture a'maudu at SDN No 101 Presidential Instruction Pattallassang, Pattallassang District, Takalar Regency. The objectives were : 1) To analyze the formation of social sensitivity in the implementation of local culture a'maudu at SDN No. 101 Pattallassang Presidential Instruction, Takalar Regency. 2) To analyze supporting factors and inhibiting for the formation of social sensitivity in the implementation of local culture a'maudu at SDN No. 101 Inpres Pattallassang, Takalar Regency. This study by the author applied, observation, and documentation methods. As for the analysis, qualitative descriptive analysis techniques, namely in the form of written or oral data from people and behavior observed so that in this case the author found out to conduct research that is through description of the actual circumstnces. In addition, the validity of the data in check applied triangulation, triangulation techniques and time triangulation. The results of this study showed that this form of social sensitivity consists of empathy, social care and building harmony. Supporting factors were parental support and teacher assistance in the classroom, while the inhibiting factors were the students' economic background and environmental influences. The implication or suggestion of this study were to always follow the implementation of local culture a'maudu that can form an attitude of sensitivity, social action and build harmony in schools so that our culture was not extinct become and still survives from time to time” .